Dispositional authenticity, perceived facilitativeness, conditions of worth, and relational outcomes in romantic relationships: empirical tests of Carl Rogers’ theory of personality and interpersonal relationships - Chen, Shun (2022)
Carl Rogers founded client-centred therapy in the 1940s and 1950s, which is a revolutionary paradigm for conceptualising human experiences in psychotherapy and counselling. Along with the extension of its applications to other fields, the term ‘person-centred approach’ was increasingly being used to replace the old term. However, Rogers left academia two years after the person-centred approach began to make an impact in social psychology. Little empirical attention has been paid to the person-centred approach in the field of social psychology; some important hypotheses remained untested. The person-centred psychology offers a systematic theory of personality and interpersonal relationships, but its potential to integrate different social psychological theories has not been fully realised. To expand the impact of the person-centred approach in social psychology, the objectives of this thesis were: examining the psychometric properties of an important psychometric tool in the person-centred approach and promoting its utility; testing the person-centred theory in opposite- and same-gender couples. Four independent but interrelated studies were conducted to achieve these objectives.